A homozygous MPZL2 deletion is associated with non syndromic hearing loss in a moroccan family. (January 2021) - Amalou, Ghita; Bonnet, Crystel; Riahi, Zied; Bouzidi, Aymane; Elrharchi, Soukaina; Bousfiha, Amale; Charif, Majida; Kandil, Mostafa; Lenaers, Guy; Petit, Christine; Barakat, Abdelhamid
Abstract: Adhesion glycoproteins are implicated in the pathophysiology of hearing loss, the most frequent inherited sensory disorder, affecting 1 in 1000 new-borns. Exome sequencing of a consanguineous Moroccan patient with mild hearing loss identified for the first time in a North African family a single homozygous mutation c.72delA in MPZL2 gene, encoding the Myelin Protein Zero-Like 2, reported as causing deafness in two other populations. Variable tandem repeat genotyping of this family revealed that the c.72delA MPZL2 allele shared a common haplotype with Turkish and Dutch families. These results confirm the pathogenicity of this MPZL2 mutation in recessive mild to moderate non-syndromic deafness.